2009
DOI: 10.1292/jvms.71.913
|View full text |Cite
|
Sign up to set email alerts
|

Duration of Maternally Derived Antibodies against Akabane Virus in Calves: Survival Analysis

Abstract: ABSTRACT. To prevent encephalomyelitis caused by Akabane virus, as observed in 2006, vaccination of calves is one of the most effective prophylactic measures. For vaccination of calves, the duration of the maternal antibodies need to be considered because these antibodies are an obstacle to the effectiveness of the vaccine. In order to estimate the age of antibody decay in calves and to find factors influencing the duration of passive immunity, we conducted survival analysis using data from nationwide sentinel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
18
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 22 publications
1
18
1
Order By: Relevance
“…There are sparse reports on the course of decay of maternal antibodies against Orthobunyaviruses in ruminants. Tsutsui et al [10] showed that dairy calves lost their maternally derived antibodies against Akabane virus at an age of approximately 4 months, while Grimstad et al [11] showed that young white-tailed deer lost their maternal antibodies against Jamestown Canyon virus at an age of 5–6 months. Our results seem to be in range with the above-mentioned studies.…”
Section: Resultsmentioning
confidence: 99%
“…There are sparse reports on the course of decay of maternal antibodies against Orthobunyaviruses in ruminants. Tsutsui et al [10] showed that dairy calves lost their maternally derived antibodies against Akabane virus at an age of approximately 4 months, while Grimstad et al [11] showed that young white-tailed deer lost their maternal antibodies against Jamestown Canyon virus at an age of 5–6 months. Our results seem to be in range with the above-mentioned studies.…”
Section: Resultsmentioning
confidence: 99%
“…Tsutsui and colleagues ( 9 ) showed that dairy calves lost their maternally derived antibodies against Akabane virus at ≈4 months of age, and Grimstad and colleagues ( 10 ) showed that young white-tailed deer lost their maternally derived antibodies against Jamestown Canyon virus at 5–6 months of age. Consistent with those findings, our results show that calves lose maternally derived SBV antibodies at ≈6 months of age and can then be effectively vaccinated against SBV.…”
mentioning
confidence: 99%
“…Maternally derived antibodies to Akabane vaccine estimated to be decayed around 4.8 months with 90% probability (Tsutsui et al, 2009). Therefore, we categorized as that VN titers from 1:4 to 1:32 (27.0%) and above 1:32 (22.8%) presume respectively positive sera from vaccinated cattle and cattle infected by wild AKAV within positive range.…”
Section: Discussionmentioning
confidence: 99%